2009
DOI: 10.1186/1471-2172-10-22
|View full text |Cite
|
Sign up to set email alerts
|

Bos taurus genome sequence reveals the assortment of immunoglobulin and surrogate light chain genes in domestic cattle

Abstract: Background: The assortment of cattle immunoglobulin and surrogate light chain genes has been extracted from the version 3.1 of Bos taurus genome sequence as a part of an international effort to sequence and annotate the bovine genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 37 publications
(44 reference statements)
2
51
0
Order By: Relevance
“…The data are highly suggestive of AIDdependent SHM in the fetal bovine IPP and spleen before exposure to exogenous antigens and imply a specific molecular mechanism to diversify the limited germline Ig repertoire. 27,34 Statistical analysis indicated strong selection of the mutated IGHV sequences in the fetal IPP and spleen ( Table 2). Negative Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data are highly suggestive of AIDdependent SHM in the fetal bovine IPP and spleen before exposure to exogenous antigens and imply a specific molecular mechanism to diversify the limited germline Ig repertoire. 27,34 Statistical analysis indicated strong selection of the mutated IGHV sequences in the fetal IPP and spleen ( Table 2). Negative Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…27,34 Antibody-diversifying mechanisms in addition to recombination are therefore likely to exist. Previous studies have suggested that these may include SHM, 6,36 GC, 7 and junctional diversity.…”
Section: Discussionmentioning
confidence: 99%
“…All non-ribosomal reads were mapped to a library containing the Bos taurus germline V, D and J genes [19, 20] (courtesy of authors Antti Livanainen and Ulrike S. Diesterbeck), and mature antibody sequences were retrieved from the DIGIT database [21] using TopHat2 software with relaxed parameters allowing for up to 30 mismatches, 50 gaps, and both should sum up to an overall edit distance of no more than 60. This was done to take into account somatic mutations and possible missing germ lines in the currently sequenced bovine antibody gene repertoire.…”
Section: Methodsmentioning
confidence: 99%
“…The Ig heavy reverse external primer was designed to amplify only Igγ1 and Igγ2 genes since Igγ3 is not expressed at the protein level 55 . In addition, because the bovine immune system expresses Ig lambda chain preferentially, 56 in this study, the Ig light reverse external primer targets all lambda genes (Ig λ 1–4) but not kappa chain genes. Out of 95 cells, 42 cells showed an Ig heavy V gene band, but the Ig lambda V gene for only 39 cells could be amplified (positive for both heavy and light V gene) and selected for sub-cloning and expression cloning.…”
Section: Resultsmentioning
confidence: 99%